2013
DOI: 10.1159/000356593
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Genetic Variants and Protein Expressions Determine the Response to Platinum Based Chemotherapy and Clinical Outcome in Patients with Advanced NSCLC

Abstract: Aim: To investigate whether the hypoxia-inducible factor-1α (HIF-1α) genetic variants and protein expression affect the chemotherapy response and the clinical outcome of patients with advanced non-small cell lung cancer (NSCLC). Methods: A total of 741 patients with histologically confirmed advanced NSCLC were recruited. Two polymorphisms of HIF-1α gene, namely, the C1772T (P582S) and G1790A (A588T) polymorphisms were determined. The HIF-1α protein expression was determined in 162 different biopsy samples by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…XRCC1 protein is involved in the BER pathway to repair DNA single-strand breaks combined with three DNA repair enzymes (DNA ligase III, DNA polymerase and PARP) [22,24,35,36]. Recently, evidence has attempted to reveal the underlying biological meaning of common XRCC1 polymorphisms (rs25487, rs25489, rs1799782), but the results of genetic studies are still inconclusive [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…XRCC1 protein is involved in the BER pathway to repair DNA single-strand breaks combined with three DNA repair enzymes (DNA ligase III, DNA polymerase and PARP) [22,24,35,36]. Recently, evidence has attempted to reveal the underlying biological meaning of common XRCC1 polymorphisms (rs25487, rs25489, rs1799782), but the results of genetic studies are still inconclusive [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that genetic Variants and protein expressions might affect the platinum-based chemotherapy response and prognosis of advanced NSCLC patients [36,37]. Platinum-based chemotherapy as a main treatment for lung cancer exerts its anti-cancer effect largely through the formation of bulky platinum-DNA adducts, which result in destabilization of the DNA double helix that otherwise blocks replication and inhibits transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not all patients can benefit from standard chemotherapy or new targeted therapies. Therefore, finding of efficient biomarkers to choose suitable treatments for individual patient is very significant for patients to acquire the maximum benefit of therapies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%